Characteristics associated with the residual risk of severe COVID-19 after a complete vaccination schedule: A cohort study of 28 million people in France - Laura Semenzato; Jérémie Botton; Jérôme Drouin; Bérangère Baricault; Marion Bertrand; Marie-Joëlle Jabagi; François Cuenot; Stéphane Le Vu; Rosemary Dray-Spira; Alain Weill; Mahmoud Zureik (Elsevier, 2022)
Summary: Background: Prior to the availability of vaccines, the risk factors for developing severe forms of COVID-19 were mostly older age and various comorbidities such as diabetes, cardiovascular diseases, mental disorders, transplantations, and kidney disease. Although vaccines have been shown to be highly effective in preventing severe forms of COVID-19, a residual risk may persist, despite vaccination, for certain population groups. Methods: The study was based on data from the national COVID-19 vaccination database (VAC-SI) coupled with the National Health Data System (SNDS), which contains comprehensive reimbursement and hospitalisation data for all of France. All people fully vaccinated by July 31, 2021, with a double-injection vaccine, i.e., the mRNA BNT162b2, mRNA-1273, or ChAdOx1 nCoV-19 vaccines, or a single dose for people with a previous confirmed SARS-CoV-2 infection were included and followed until August 31, 2021. Cox proportional hazard models were performed to estimate adjusted hazard ratios (aHR) for COVID-19-related hospitalisation or in-hospital death associated with age, gender, deprivation index, comorbidities, and immunosuppressive or oral corticosteroid therapy from day 14 after full-vaccination. Findings: In a population of 28,031,641 fully vaccinated individuals with an average follow-up of 80 days, 5,345 (87 hospitalisations per 100,000 person-years) were hospitalised for COVID-19 and 996 (16 in-hospital death per 100,000 person-years) died in hospital. In multivariable analysis, a higher risk was observed with increasing age, male gender, and social deprivation. Most of the 47 chronic conditions considered were positively associated with an increased risk of COVID-19-related hospitalisation and a slight excess risk of death. The risk of hospitalisation and in-hospital death for COVID-19 also increased with the use of immunosuppressants (aHR 3.3 [2.8-3.8] and 2.4 [1.7-3.5], respectively) and oral corticosteroids (aHR 2.8 [2.5-3.1] and 4.1 [3.3-5.1]).Less than 10% (519/5,345) of hospitalised cases and 2% (24/996) of those who died in hospital had no identified comorbidities. There was a strong association between an increasing number of comorbidities and the risk of hospitalisation and in-hospital death (e.g., 5+ versus none, aHR 10.1 95%CI 9.0-11.5 and 17.8 95%CI 11.5-27.4, respectively). Interpretation: Although vaccination has dramatically reduced the occurrence of severe forms of COVID-19, a residual risk remains for the elderly, immunocompromised, and polypathological populations and warrants complementary preventive measures. Funding: None.